Professional Training of the Future Primary School Teachers in the Czech Republic: Regulatory Bases (1989–2005) - Кateryna Binytska (Педагогічний дискурс)
The analysis of regulatory bases of professional training of the future primary school teachers in the Czech Republic has been made in the article. The relevance of this issue is also linked to the effective implementation of updated legal and regulatory basis of educational space of Ukraine according to European standards. The article reflects the scientific researches of domestic and foreign comparativists as for the professional preparation of the future teachers of primary school in the Czech Republic. It is mentioned that in the process of reforming the sphere of education, the Czech Republic used the experience of other European countries and recommendations of international organizations. The attention is focused on the fact that the first official document which determined the course of reforms was the Law «On Quality and Accountability in Education», prepared by the Ministry of education in 1994, which became the basis of the adopted in 2001, National programme of education development in the Czech Republic (so called White Book) that became the impetus for the future reforms in this area. It is noted that in the Czech Republic since 2001 in the national programme for the development of the education sector highly qualified teacher is considered as a major factor in the development of the education system.